Pengujian Mutu Benih Beberapa Jenis Tanaman Hortikultura yang Beredar di Bali - NI NYOMAN DWI RESPITA NINGSIH; I GUSTI NGURAH RAKA; I KETUT SIADI; GUSTI NGURAH ALIT SUSANTA WIRYA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Seed Quality Testing Several Types of Horticultural Crops Circulating in Bali This study aims to determine the physical quality, viability, and vigor seeds of several types of horticultural crops those circulating in Bali. This research was conducted at Breeding and Seed Technology Laboratory and Plant Disease Laboratory of Udayana University Faculty of Agriculture, which lasted from February to April 2015. The method used is seed testing method with duplo system and using T-Test with three replications. The types of seeds that are tested for their quality consist of seven species: mustard, long bean, eggplant, ercis, cucumber, cayenne, and cabbage. The variables observed were physical quality (moisture content), viability (seed germination), and vigor (synapticity of seed growth). The results showed that the seeds of some horticultural crops circulating in the market in Bali have a pretty good quality. This can be seen from the physical quality test of seeds in the form of moisture content, almost all seeds have a relatively safe water content for storage. The result of seed quality test of percentage of seed germination gain between 90.33% - 97.33% in laboratory test is very good because it is above the standard germination value. The result of the simultaneous vigor test grew up to 59.00% - 69.00% is a good enough vigor value because it is at a level above 50%.